Negation and Negative Concord in Georgian Sign Language - Pfau, Roland; Makharoblidze, Tamar; Zeijlstra, Hedde (Frontiers in Psychology, 2022)
Negation is a topic that has received considerable attention ever since the early days of sign language linguistics; also, it is one of the grammatical domains that has given the impetus for sign language typology. In this paper, we offer a typological and theoretical contribution to the study of sign language negation. As for the typological side, we add Georgian Sign Language (GESL) to the pool of languages investigated. Our description reveals that GESL displays a number of typologically unusual features: a considerable number of negative particles, including emphatic, prohibitive, and tense-specific particles; specialized negative modals; and a wide range of possibilities for Negative Concord (NC) involving two manual negative signs, including a unique tense-specific instance of NC. Most of the patterns we report – available negative particles, their clausal position, and NC possibilities – are clearly different from those attested in spoken Georgian. As for the theoretical contribution, we investigate how the highly complex GESL negation system compares to existing taxonomies of NC and Double Negation systems, and we conclude that GESL aligns with certain languages that have been classified as atypical NC languages.